Beyond Assessment of Quality of Life in Schizophrenia - Awad, A. George; Voruganti, Lakshmi N.P (Springer International Publishing : Imprint: Adis, 2016)
This book fills a significant research gap in how to integrate quality of life data into relevant clinical care plans, and to broaden its applicability to pharmacoeconomic studies of antipsychotic medications and health policy decision-making. It also presents an argument for reformulating the concept of health-related quality of life in schizophrenia as a bio-psycho-social construct, which provides an opportunity to better explore the many factors underpinning the concept itself. Internationally renowned experts from different scientific backgrounds and scopes of expertise each make arguments for the need to invigorate quality of life as a concept in schizophrenia, by broadening its usefulness for clinical and research efforts. The book represents an important addition to the extensive contributions of its editors, Dr. A. George Awad and Dr. Lakshmi N.P. Voruganti, to the field of quality of life.